THE INFLUENCE OF MANURE (CHICKEN, GOAT, HORSE, AND COW) ON THE GROWTH AND YIELD OF MUSTRAD GREENS - Yohanes Gabriel Santio Bien; Frengky Lambu Apu; Ade Irma Sulistiani (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Green mustard (Brassica rapa var. parachinensis L.) is one of the vegetables widely consumed by the community due to its high nutritional value. Efforts to increase the production of green mustard can be carried out thru the use of organic fertilizers, one of which is manure. This study aims to determine the effect of various types of manure on the growth and yield of green mustard plants and to identify the type of manure that provides the best results. The research was conducted in Kesetnana Village, Mollo Selatan District, South Central Timor Regency, East Nusa Tenggara Province from April to June 2026. The research used a Completely Randomized Design (CRD) with one factor consisting of five treatments, namely without manure (A0), chicken manure (A1), cow manure (A2), horse manure (A3), and goat manure (A4), with three replications. The parameters observed include plant height, number of leaves, leaf width, stem diameter, stem length, root length, and fresh plant weight. Data were analyzed using analysis of variance (ANOVA) followed by the Duncan Multiple Range Test (DMRT) at a 5% significance level. The research results showed that the application of various types of manure had an effect on the growth of green mustard plants. The treatment with goat manure (A4) yielded the best results in terms of plant height (29.33 cm), leaf width (13.00 cm), stem length (13.16 cm), and root length (10.66 cm). Meanwhile, the treatment with cow manure (A2) produced the highest number of leaves, which was 9.33 leaves. In general, the use of manure can enhance the growth and yield of green mustard plants compared to without the application of manure.